Frank Einstein & the Antimatter Motor - Scieszka, Jon; Biggs, Brian (New York : Amulet Books, 2014)
In his Grandpa Al's garage workshop, child genius Frank Einstein tries to invent a robot that can learn on its own, and after an accident brings wisecracking Klink and overly expressive Klank to life, they set about helping Frank perfect his Antimatter Motor until his archnemesis, T. Edison, steals the robots for his doomsday plan.
Keywords: Robots -- Fiction; Inventors -- Fiction; Humorous Stories; Science fiction; JUVENILE FICTION / Science & Technology; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Science Fiction